Política de habitação e direito à cidade no município de Embu/SP - 2001-2008 - Machado, Bruna Maria Eloy (2008)
This Masters thesis has as its objective of study the analysis of the Municipal Habitation Politics of the city of Embu/SP implemented during the 2001-2008 period and its contribution to effect the right to the city to the local population, primarily, to the low income segments of the society. The general objective of this investigation consisted on knowing and analyzing the Municipal Habitation Politics of Embu and the process of effect of the right to the city trough the local participatory management, of the Municipal Directory Plan and the Municipal Habitation Politics. It was defined as hypothesis that the Municipal Habitation Politics of Embu is partially contributing to effect of the right to the city to the local population, primarily, to the low income segments. It was adopted as the methodological path to this research development the qualitative approach, including bibliographical, documental and Field research and also the researcher experience. As methodological instruments was used a form to characterize the housing associations of the city and the semi-structured interview. There were made 7 interviews, with specific scripts for each group of people. To the analysis of the collected data was used the content analysis technique. The reference concepts adopted were: City, Right, Habitation and Democratic Management, in an interdisciplinary approach. The results showed a positive improvement on the implement of politics in the sense of building up a public politics, committed with the qualitative deficit reduction of habitation in irregular settlements and with improvement of the urban life quality. It was also verified the process of creating a city democratic and participatory management too. There were also identified limitations, mainly, on the finances for habitation issues, the missing of an urban and intersectorial development politics and also, an incipient ownership of subjective right to the city